TEORI HERMENEUTIKA HUKUM KHALED M. ABOU EL-FADL Membongkar Fiqh Otoriter Membangun Fiqh Otoritatif - Zayyadi, Ahmad (Al-Mazaahib: Jurnal Perbandingan Hukum, 2012)
The hermeneutic approach in law is the new discourse. It has its unique, because of Khaled M. Abou El-Fadl‟s idea. It tries to deconstruct the law authoritarianism phenomena which bring to the new fiqh that is more authoritative and applicable in the contemporary fiqh discourse (Islamic Jurisprudence). Law hermeneutic he formed is tend to a text interpretation authority through negotiating the text, the author and the reader. The set of very basic methods are the basic assumptions such as assumption based on the values, methods, reason, and belief. The four assumptions according to Khaled M. Abou El-Fadl can‟t be leave in developing law theory and interpretation. The article aims to create the new meaning more objective, authoritative which is not included in the interpretation authoritarianism conducts, especially in the creating law texts more authoritative and humany.